PENERAPAN MODEL COOPERATIVE LEARNING METODE PEER LESSONS SEBAGAI UPAYA PENINGKATAN PRESTASI BELAJAR EKONOMI DI MA AL-MUJADDADIYYAH MADIUN - Sudjianto Sudjianto (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2013)
Many factors affect academic achievement, one of which is the teacher. Teachers need to use teaching methods that are relevant to the content and objectives to be achieved in the learning. One method that can improve student achievement is the method of Peer Lesson. By applying the method of Peer Lesson, students will become active in the learning process because one of the friends group that knows more about the matter can explain the material to friends who are not informed about.       This research was classroom action research by applying the model Cooperatif Peer Learning Lesson method. The subjects in this study were students of class X MA Al-Mujaddadiyyah Madiun school year 2012/2013. The data was collected using the observation sheet to assess learning ability and questionnaires for data sheet studentinterest. Analysis of data for learning and student interest using descriptive qualitative analysis, quantitative data by calculating the percentage of first cycle and second cycle.       The results showed that the use of methods to improve the ability Peer Lesson Study abroad and student interest. Improved learning ability of students can be seen from the increasing number of students who are active in the second cycle, increase student achievement can be seen from the increasing student mastery learning and getting better value from each of these aspects include: the results of the discussion of expression, accept the opinion of the right reasons , care of the group, do the work and help a friend.